Implementation of Reading Aloud and the Power of Two Strategies in Improving the Ability to Read and Memorize Al-Quran Verses in Senior High Schools - Silvia Vitaloka; Teguh Hariyanto; Ujang Ikin (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2026)
Qur’an learning in Islamic Religious Education plays an important role in developing students’ ability to read and memorize Qur’anic verses while instilling moral values. However, the ability to read and memorize verses regarding the prohibition of adultery among tenth-grade students at SMA Negeri 1 Cicurug remains low due to less interactive teaching methods. This study aims to improve students’ ability to read and memorize Qur’anic verses through the implementation of the Reading Aloud and The Power of Two strategies. The research used a Classroom Action Research method conducted in two cycles, including planning, implementation, observation, and reflection, with 46 students as subjects. The results showed a significant improvement, with learning mastery increasing from 40% at the initial stage to 60% in Cycle I and 85% in Cycle II, accompanied by increased student activity and teacher performance in learning implementation. The study concludes that interactive and collaborative learning effectively enhances students’ ability to read and memorize Qur’anic verses. The implication is that these strategies can be applied continuously in other classes to improve the quality of Qur’an learning and support the development of students’ religious character.